A systematic review of adherence to group interventions in psychosis: do people attend?. Issue 5 (16th April 2021) - Sedgwick, Ottilie; Hardy, Amy; Newbery, Katie; Cella, Matteo
Abstract: Background: Evidence supports the use of group therapy for symptom reduction and improving functioning in people with psychosis. However, research guidelines highlight the importance of establishing the feasibility of interventions. Adherence is an important indicator of feasibility and an essential step in supporting the development of the evidence base for group interventions. This review aims to estimate adherence, and possible barriers and facilitators, to psychotherapeutic groups in people with psychosis. Methods: Embase, Ovid MEDLINE and PsycINFO databases were searched for cross-referencing terms related to group therapy and psychosis. Studies were assessed against inclusion criteria and methodological quality was evaluated. Data wasextracted from each paper including the average session attendance, demographic, clinical, study and therapy-related characteristics and the impact of these on adherence levels evaluated. Results: Fifty-nine original research papers were included, reporting on 52 independent studies which consisted of 66 therapy groups comprised of 2109 participants. Average adherence was 76.4% (s.d. = 17.4). Adherence was improved by receiving incentives and was higher in participants of older age. Study sample size was inversely associated with adherence levels. Study quality was variable with approximately 61.5% found to be at risk of bias. The results support the feasibility of group therapy and suggest that adherence in people with psychosis is not dissimilar to those for people experiencing common mental health difficulties. These findings, alongside efficacy evidence, support the use of group interventions in people with psychosis but also highlight the need for further high-quality research on the efficacy for these approaches.